Description and Geography of Euphorbia L.Species in the Flora of Uzbekistan - Soatova Dilfuza (Zien Journals, 2022)
Based on the materials of the herbarium of the Institute of Botany of the Academy of Sciences of the Republic of Uzbekistan (TASH), scientific literature and cadastral data of the flora of Uzbekistan, reviews and identification of the genus Euphorbia L. were given. Herbarium specimens of the category in the unique herbarium fund of the institute have not been fully processed and analyzed. The article provides information on species found in the flora of Uzbekistan and their distribution. The distribution of species was given on the basis of monographs on the plant cadastre and flora of the regions.
Keywords: genus; species; Euphorbia; Uzbekistan